Hubungan Kepercayaan Diri Degan Keterampilan Komunikasi Antar Pribadi Siswa Kelas VII MTsN 8 Agam - Muharani, Aulia; Kamal, Muhiddinur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Researh motivated by probleems found in the seventh grade of MTSN 8 Agam that it was indicated that some students experienced problems in inter personal commuinication and self-connfidence. The results of observatiions and opinons of guidance and counnseling teachers conducted by researchers at MTsN 8 Agam indicated that some students had difficulty opening up, lackd empathy, lacked respect for other people's opinions, and were unsure of their own abilitties. To find out the relationship and magnitude of the relationhip between self-confidence and interpersonal communication is the aim of the reserch. The method used in the research is quantitative correlational using hypothesis testing, namely the Pearson product moment correlation test. The results obtained from the reseach are the correct correlation and sig value. (2 tails) 0..01 < 0..05 and rcount 0.735 > rtable 0.208. The correlation coefficient level of correlation value s is 0.735, meaning that the degree of closeness of the relatinship between self-confidence (X) and interpersonal communication (Y) is high or strong, and it can be concluded that the relationship betwen self-confidencce and inter personal communication for class VII students at MTsN 8 Agam is significantly related.